2009
DOI: 10.1016/j.cbpa.2009.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response of brain tissue oxygenation to environmental hypoxia in non-sedated, non-anesthetized arctic ground squirrels

Abstract: The present study examined the physiological mechanisms of the responses of brain tissue oxygen partial pressure (P t O 2 ), brain temperature (T brain ), global oxygen consumption V̇o 2 , and respiratory frequency (f R ) to hypoxia in non-sedated and non-anesthetized arctic ground squirrels (Spermophilus parryii, AGS) and rats. We found that 1) in contrast to oxygen partial pressure in blood (P a O 2 ), the baseline value of P t O 2 in summer euthermic AGS is significantly higher than in rats; 2) both P t O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 47 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…This study confirms, in unanesthetized animals, the observation that Pto 2 will drop significantly with an acute decline in inspired Po 2 Ma et al, 2009). In mammals, a decline in Fio 2 of 50% would be similar in the reduction of oxygen delivery to that which occurs with ascent to approximately 1/2 atm pressure at an elevation of approximately 6000 m, depending on latitude.…”
Section: Pto 2 In Brain During Normoxia and Acute Hypoxiasupporting
confidence: 86%
See 1 more Smart Citation
“…This study confirms, in unanesthetized animals, the observation that Pto 2 will drop significantly with an acute decline in inspired Po 2 Ma et al, 2009). In mammals, a decline in Fio 2 of 50% would be similar in the reduction of oxygen delivery to that which occurs with ascent to approximately 1/2 atm pressure at an elevation of approximately 6000 m, depending on latitude.…”
Section: Pto 2 In Brain During Normoxia and Acute Hypoxiasupporting
confidence: 86%
“…As such, it is important to understand the mechanisms that regulate oxygen delivery and establish oxygen levels in the brain. Under acute conditions, it is known that oxygen content is not held constant, because acute reduction in the partial pressure of arterial oxygen (Pao 2 ) or cerebral blood flow (CBF) will cause a reduction in Pto 2 (Leniger-Follert et al, 1975;Hoffman et al, 1996;Nwaigwe et al, 2000;Ma et al, 2009). Increased energy demand in the brain also results in increases in Pto 2 (Leniger-Follert et al, 1975), probably owing to a disproportionate increase in flow relative to metabolic rate (Kim et al, 1999).…”
mentioning
confidence: 99%
“…This difference in V O2 during hyperoxia was not caused by body mass scaling as discussed in our previous study (Ma et al, 2009), where we found that V O2 during 8% O 2 exposure was significantly lower in euthermic AGS than in rats.…”
Section: Hyperoxic Response and Metabolic Rate For Osupporting
confidence: 83%
“…P t O 2 returns to the normal level after hypoxic exposure ends and ambient air inhalation resumes, indicating that AGS brain tolerates hypoxic conditions (Ma et al, 2009). When both euthermic AGS and rats are exposed to 100% O 2 inhalation, sO 2 in rats is not affected by 100% O 2 inhalation; however, sO 2 is significantly increased in AGS blood, but remains at a lower level than in rats (Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation